1984
DOI: 10.1161/01.str.15.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Local vascular response to change in carbon dioxide tension. Long term observation in the cat's brain by means of the hydrogen clearance technique.

Abstract: (617) ALTHOUGH ARTERIAL carbon dioxide tension (PaCO 2 ) has often been confirmed as a prominent factor of circulatory control in the central nervous system (CNS) since regional CBF measurements were performed, 1 " 12 the quantitative relationship between local cerebral blood flow (ICBF) and PaCO 2 is not yet clear. Within physiologic ranges of PaCO 2 , the vascular response has been described to be linear 2 "5 l0 " but also as an exponential function.' 8 9 n This has led to uncertainty in calculations of CBF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…A considerable difference was found between the caudate nucleus and the cerebellar cortex in CBFr and the absolute CO 2 reactivity, but the relative CO 2 responses in the cerebrum and the cerebellum were similar. These results are in agreement with those in earlier studies, which showed that, although the absolute values of CO 2 reactivity might be different due to a greater CO 2 response in better perfused areas, the relative CO 2 reactivity is uniform throughout the CNS (Ackerman 1973, von Kummer 1984. In agreement with our results, in the two studies where the cerebral cortical and basal ganglion CO 2 reactivities were compared in cats using the HC method, no difference was found , von Kummer 1984.…”
Section: Regional Differences In Cbf Response Induced By Co 2 and Acesupporting
confidence: 93%
See 1 more Smart Citation
“…A considerable difference was found between the caudate nucleus and the cerebellar cortex in CBFr and the absolute CO 2 reactivity, but the relative CO 2 responses in the cerebrum and the cerebellum were similar. These results are in agreement with those in earlier studies, which showed that, although the absolute values of CO 2 reactivity might be different due to a greater CO 2 response in better perfused areas, the relative CO 2 reactivity is uniform throughout the CNS (Ackerman 1973, von Kummer 1984. In agreement with our results, in the two studies where the cerebral cortical and basal ganglion CO 2 reactivities were compared in cats using the HC method, no difference was found , von Kummer 1984.…”
Section: Regional Differences In Cbf Response Induced By Co 2 and Acesupporting
confidence: 93%
“…In agreement with our results, in the two studies where the cerebral cortical and basal ganglion CO 2 reactivities were compared in cats using the HC method, no difference was found (Symon et al. 1973, von Kummer 1984). The CO 2 response in the cerebellum has been determined in only a few studies.…”
Section: Regional Differences In Cbf Response Induced By Co2 and Acetsupporting
confidence: 92%
“…This mean velocity value is the time-averaged mean calculated from the spectral outline of the maximal velocities by the TC2-64 instrument [3]. End-tidal carbon dioxide correlates to arterial Pco 2 , reflecting the intrinsic effects of carbon dioxide at the arteriolar site, that is, the resistance vessels in the MCA territory [5,6]. The vasodilatory effect of carbon dioxide is attributed to the effect on these resistance vessels, rather than to the minute changes in the diameter of the basal cerebral arteries [7,8].…”
Section: Discussionmentioning
confidence: 99%